Effects of the Age Process on Aggregate Discounted Claims - Ghislain Léveillé (Risks, 2018)
In this document, we examine the effects of the age process on aggregate discounted claims by studying the conditional raw and joint moments, the moment generating function and the distribution function of the increments of compound renewal sums with discounted claims, taking into account the past experience of an insurance portfolio.